Cuestionário de gratitud de 20 ítems (G-20) : tradução e adaptação transcultural para idosos do Brasil - Viana, Susy Ane Ribeiro (2017)
The construction and adaptation of instruments are necessary to aggregate methods of psychological evaluation that aim to investigate aspects of health promotion and quality of life, it is particularly noticed the importance of new instruments that contemplate the elderly. The literature has shown gratitude as a protective factor and as a provider of subjective well-being for the elderly. Therefore, the central axis of this study is the cross-cultural translation and adaptation of the Cuestionário de Gratitud de 20 ítems (G-20) prepared by Bernabé-Valero et al (2014) in Spain, directing the instrument to the elderly Brazilian population. It was chosen as the method of adaptation the ten-step process of Beaton et al. Al (2002): 1) Conceptual definitions and literature review; 2) Contact with the author; 3) Translation; 4) Synthesis of translations; 5) Backtranslation; 6) Analysis of Judges; 7) Modifications and readjustments; 8) Pilot Study; 9) Final version readjustments and application in a larger sample; And, 10) Psychometric Analyzes of the instrument. The Brazilian version will maintain the G-20 nomenclature, adding the name "G-20-IB Elderly Gratitude Scale" (Brazilian Elderly) in its final title. Six bilingual translators participated in the study, of which 3 were Brazilian and 3 were foreigners (stage 3); Seven judges, two specialists and five non-specialists (stage 6); 38 elderly (step 8); And 80 elderly (stage 9), from three Brazilian states. Descriptive statistical analyzes (average, standard deviation, percentages and percentiles) were performed for the analysis among judges. The concordance index will be evaluated using the Fagundes method and the Kappa index. Internal consistency was measured using Cronbach's Alpha. The G-20 IB presented suitability between judges concordance analyzes, where k = 1. As well as, presented Alpha of Cronbach equal to α = 0.81 demonstrating optimal adequacy, suggesting that the instrument has a good level of convergence between the items. Further studies are still needed for the psychometric validation of the G-20 IB, however this study was able to present a premise of other studies that may still be performed with this new evaluation instrument. Gratitude is linked directly as we shape interpersonal relationships and personal existential senses. It has a motivating and pro-social factor, which intensifies emotions of subjective well-being towards healthy aging. The contribution of this study would be to help in the elaboration of new knowledge and intervention techniques for the elderly that prioritize the use of preventive and non-pharmacological tactics.